Investigation of the mechanical properties changes for multimaterial composite 3d printing - Lee, Zhan Shin (2023)
3D printing is a type of additive manufacturing that manufacture that creates a three-dimensional object by adding material layer by layer. In this study, the Fused Deposition Modeling (FDM) 3D printing is used. The purpose of this research is to improve the overall mechanical properties of 3D printed parts and eliminate the weakness by combining 2 different materials into 1 part. In traditional single-material printing, the choice of material used to create a part is limited to a single material. This limitation results in reduced mechanical properties and application limitations for the 3D printed parts. However, the introduction of multi-material 3D printing has overcome these limitations by combining different materials in one 3D printed parts. Multi-material printing is capable of printing composite materials, which can significantly improve the overall mechanical properties of printed parts. The composite materials are formed by combining two or more materials that complement each other, thus eliminating the weakness of individual materials and improving overall properties. The use of composite materials in printing also allows for the creation of parts with specific functions and purposes. Overall, multi-material printing has revolutionized the capabilities of 3D printing and expanded its potential applications, paving the way for new and innovative designs in various industries. There will be three main experiments in this study to determine the mechanical properties of 3D printing material, which is tensile test, flexural test and Izod impact test. All three experiments are done to determine the mechanical properties of mono material 3D printing. The experimental data are then inserted into Ansys simulation to simulate the mechanical properties of multi material 3D printing parts. Lasty, 2 sets of multi material 3D printed specimens are printed to validate the simulation data by doing those 3 experiments. The simulation shows that the combination of PLA and PETG specimens can provide the highest ultimate tensile strength and modulus with the moderate flexural strength and modulus. For the PLA and PETG combination 3D printing, the tensile test of this combination is 37.15 MPa and the flexural strength is 46.35MPa, the impact resistance is 294.64 J/m. The study also proves that most of the simulation model are accurate but there are still some improvements need to be done to increase the accuracy of the simulation model. The differences between the simulation and experimental results are lesser than 20%.